Doing narrative research - Andrews, Molly; Squire, Corinne 1958-; Tamboukou, Maria 1958- (Los Angeles, California SAGE, 2013)
"Written by an international team of experts in the field, the second edition of this popular text considers both the theoretical underpinnings and practical applications of narrative research. The authors take the reader from initial decisions about forms of narrative research, through more complex issues of reflexivity, interpretation and the research context. Existing chapters have been updated to reflect changes in the literature and new chapters from eminent narrative scholars in Europe, Australia and the United States have been added on a variety of topics including narratives and embodiment, visual narratives, narratives and storyworlds, new media narratives and Deleuzian perspectives in narrative research. This book will be invaluable for all students, researchers and academics looking to use narrative methods in their own social research."--Publisher's website
Introduction: What is Narrative Research? / Maria Tamboukou and Molly Andrews, Corinne Squire -- Narratives of Events: Labovian Narrative Analysis and its Limitations / Wendy Patterson -- From Experience-Centred to Socioculturally-Oriented Approaches to Narrative / Corinne Squire -- Analysing Narrative Contexts / Ann Phoenix -- A Foucauldian Approach to Narratives / Maria Tamboukou -- Practising a Rhizomatic Perspective in Narrative Research / Gerrit Loots, Kathleen Coppens and Jasmina Sermijn -- Bodies, Embodiment and Stories / Lars-Christer Hydén -- Seeing Narratives / Susan E Bell -- Doing Research 'On and Through' New Media Narrative / Mark Davis -- Approaches to Narrative Worldmaking / David Herman -- Looking Back on Narrative Research: An Exchange / Phillida Salmon and Catherine Kohler Riessman -- Never the Last Word: Revisiting Data / Molly Andrews -- Narrating Sensitive Topics / Margareta Hydén -- The Public Life of Narratives: Ethics, Politics, Methods / Paul Gready -- Concluding Comments / Catherine Kohler Riessman -- Afterword: The Monkey Wrenches of Narrative / Jens Brockmeier.
Previous edition: 2008
Includes bibliographical references and index.
Keywords: Narrative inquiry (Research method).; Social sciences -- Research -- Methodology